Analisis Perkembangan Kebijakan Fiskal Dalam Prespektif Ekonomi Islam - Nisa Oktaviani,; Anjely Wahyuni,; Wiwid Yulinda Sari,; Faisal Hidayat, (Jurnal Mutiara Ilmu Akuntansi, 2023)
This article discusses the analysis of the development of fiscal policy in the perspective of Islamic economics. fiscal policy is a fiscal policy is a policy made by the government with the aim of regulating income and expenditure in the country in order to maintain stability and encourage economic growth. In Islamic economics, fiscal policy is intended as a tool to create a goal in accordance with sharia principles. What can be said that the objectives of sharia are: maintaining the welfare and security of society, life, maintaining faith, wealth, intellect, and ownership. In Islamic economics there are principles that must be obeyed in carrying out fiscal policy according to sharia / according to Islam. One of these principles is the principle of muamalah, where every Muslim will be freed in terms of carrying out an activity or business activity that has been made obligatory in Islam.